2022
DOI: 10.3389/fpsyg.2022.915817
|View full text |Cite|
|
Sign up to set email alerts
|

Perception, Beliefs, and Causal Attribution of Autism Early Signs in Ecuadorian General Population

Abstract: The identification and diagnosis of children with autism currently rely on behavioral presentation and developmental history. Cultural norms and other socio-demographic factors can influence what is expected or non-expected behaviors in a developing child. Perceptions, beliefs, and causal attribution of early signs can influence families’ help-search behaviors. Lack of recognition of autism’s first manifestations can critically delay the age of diagnosis, the provision of informed guidance to families, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…A second study ( Buffle et al, 2022 ), conducted on 183 paediatric professionals, indicated a low number of cases of autism identified during participant’s professional life, with 62% of participants reporting not having identified ASD cases during their professional life. This study also identified several barriers consistent with those identified in other countries, including limited knowledge of screening formal application, lack of time, lack of resources to refer and information to provide families, and fear of unnecessarily alarming families ( Buffle et al, 2022 ).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…A second study ( Buffle et al, 2022 ), conducted on 183 paediatric professionals, indicated a low number of cases of autism identified during participant’s professional life, with 62% of participants reporting not having identified ASD cases during their professional life. This study also identified several barriers consistent with those identified in other countries, including limited knowledge of screening formal application, lack of time, lack of resources to refer and information to provide families, and fear of unnecessarily alarming families ( Buffle et al, 2022 ).…”
Section: Introductionsupporting
confidence: 63%
“…This procedure can play an important role in primary care routines. Combined with a short, validated and culturally adapted questionnaire, it can contribute to eliminating barriers to screening and identification that have previously been reported by Ecuadorian paediatricians ( Buffle & Gentaz, 2019 ; Buffle et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent health literacy may further contribute to autism services use for young children [94]. A misunderstanding of early signs as manifestations of a developmental condition may lead to increased stigma and non-conventional explanations [95][96][97]. Parents with LHL whose child has recently been diagnosed with autism spectrum disorder (ASD) report an information gap and a lack of resource adaptation during diagnosis [98].…”
Section: Barriers To Autism Recovery and Progressionmentioning
confidence: 99%